Model-driven development for pervasive information systems - Fernandes, José Eduardo (2010)
This chapter focus on design methodologies for pervasive information systems (PIS). It aims to contribute for the efficiency and effectiveness on software development of ubiquitous services/applications supported on pervasive information systems. Pervasive information systems are composed of conveniently orchestrated embedded or mobile computing devices that offer innovative ways to support existing and new business models. Those systems are characterized as having a potential large number of interactive heterogeneous embedded/mobile computing devices that collect, process, and communicate information. Additionally, they are target of high rates of technological innovations. Therefore, changes on requirements or in technology demands for frequent modifications on software at device and system levels. Software design and evolution for those requires suitable approaches that cope with such demands and characteristics of pervasive information systems. Model-driven development approaches (which essentially centre the focus of development on models, and involves concepts such as Platform-Independent Models, Platform-Specific Models, model transformations, and use of established standards) currently in research at academic and industrial arenas to design of large systems, offer potential benefits that can be applied to design and evolution of these pervasive information systems. In this chapter, we raise issues and propose strategies related to the software development of PIS using a model-driven development perspective.